2005
DOI: 10.1002/hlca.200590126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Border between Concerted and Two‐Step Pathways of 1,3‐Dipolar Cycloadditions of Organic Azides to Cyclic Ketene N,X‐Acetals. – Synthesis and 15N‐NMR Spectra of Zwitterions and Spirocyclic Cycloadducts

Abstract: Cyclic ketene N,X‐acetals 1 are electron‐rich dipolarophiles that undergo 1,3‐dipolar cycloaddition reactions with organic azides 2 ranging from alkyl to strongly electron‐deficient azides, e.g., picryl azide (2L; R1=2,4,6‐(NO2)3C6H2) and sulfonyl azides 2M–O (R1=XSO2; cf. Scheme 1). Reactions of the latter with the most‐nucleophilic ketene N,N‐acetals 1A provided the first examples for two‐step HOMO(dipolarophile)–LUMO(1,3‐dipole)‐controlled 1,3‐dipolar cycloadditions via intermediate zwitterions 3. To set th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…[9] NMR spectra of solutions in potassium [D 2 ]dihydrogen phosphate/deuterium oxide that were obtained from 1a and d showed that protonation drastically changes the spirocyclic structures. The spiro carbon-13 signals at 100-105 ppm [9,10] are no longer observed while 1 H and 13 C NMR signals that are characteristic of 5-alkyl-1,4-dimethyltetrazolium ions make their appearance. [11] These results indicate that the dihydrotriazole ring of 1a and d was opened to yield a triazene.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…[9] NMR spectra of solutions in potassium [D 2 ]dihydrogen phosphate/deuterium oxide that were obtained from 1a and d showed that protonation drastically changes the spirocyclic structures. The spiro carbon-13 signals at 100-105 ppm [9,10] are no longer observed while 1 H and 13 C NMR signals that are characteristic of 5-alkyl-1,4-dimethyltetrazolium ions make their appearance. [11] These results indicate that the dihydrotriazole ring of 1a and d was opened to yield a triazene.…”
Section: Resultsmentioning
confidence: 92%
“…The observed dynamic phenomenon is due to restricted rotation around the C(5)-CHtBu bond. In comparable zwitterions that differ from 2dX only by a triazenide side chain instead of the 3-methyltriazen-1-yl group, rotation around the C(5)-CHtBu bond is even completely frozen on the 1 H, 13 C, and 15 N NMR time scales employed, [10,18] and the tert-butyl groups adopt a conformation perpendicular below (or above) the ring planes in the solid state. [18] N-Alkyl-NЈ-phenyltriazenes prefer the 3-alkyl-1-phenyl tautomer, in which the phenyl group is conjugated with the azo group.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Such a change of mechanism has been studied for cycloadditions of thiocarbonyl ylides [9] (for a review, see [10]) and sulfonyl azides [11] [12]. A similar cooperation of steric and electronic effects is described here for cycloadditions of di(tert-butyl)diazomethane (4).…”
mentioning
confidence: 87%